In vitro penetration through the skin layers of topically applied glucocorticoids. Issue 10 (20th June 2018) - Carrer, Victor; Alonso, Cristina; Oliver, Marc Adrià; Coderch, Luisa
Abstract: Corticoids are actives widely used in the treatment of skin diseases. This work aims to study the penetration of 3 corticoids (betamethasone, clobetasol, and flurandrenolide), their relationship with their Log D values and the effects of the vehicles. The 3 compounds were applied on a Franz‐type diffusion cell in propylene glycol solution and their respective commercial creams and ointments. The active amounts found in the stratum corneum, epidermal, and dermal layers of the skin were investigated. Their diffusions were greatly affected by the formulation; moreover higher amounts of substance in the epidermis and dermis were detected in ointments than in creams. The enhancement effect of propylene glycol was also observed. The differences between the 3 substances could be related to their lipophilicity, molecular structure, and molecular weight. The more hydrophobic compounds (clobetasol and betamethasone) are present in higher amounts in the epidermis and dermis, while the hydrophilic compound (flurandrenolide) is mostly present in the receptor fluid. Abstract : In this work skin diffusion of three different corticoids (betamethasone, clobetasol and flurandrenolide) are studied in propylene glycol solutions and their respective commercial creams and ointments using Franz diffusion cells. Our results showed that their diffusion was greatly affected by the formulation. Moreover, their physico‐chemical properties could be also related with their different drug disposition and efficacy.